Safety and Efficacy of Thrombolytic Therapy Using rt-PA (Alteplase) in Acute Ischemic Stroke - Sivanandy, Palanisamy (International Scholarly Research Network, 2011)
The aim of this study was to evaluate the efficacy and safety of thrombolytic therapy. Our study enrolled 23 patients out of which 2 patients died due to ICH; we also found that only 39% of patients reached hospital within stroke window, and for those treated, mean NIHSS during admission was 14.0, but drastic improvement was shown after 24 hours of treatment, that is, 9.89 (P < 0.0001), and at discharge, it was 5.1 (P < 0.0001) which showed a clear impact of the treatment, and around 60% of patients were discharged within an mRS score of 1 and 2. Hence, it was found that thrombolytic therapy was beneficial, efficacious, and safe if used within 3 to 4.5 hours.